Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Cultural heritage in the Arctic and Antarctic regions - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2004)
Keywords: Antarktis; kulturminnevern; kulturvern; polarområdene

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Amundsen og hans aeronauter - Berg, Roald (Norsk polarhistorie, 2004)
Keywords: Antarktis; Norvegia ekspedisjoner; flyging; flyvere; oppdagelsesreiser

Den første norske oljealderen - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Sørishavet; ekspedisjoner; hvalfangstindustri; hvalolje; pelagisk

Polarturisme - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Antarktis; polarområdene; turisme

Ein grådig fangstnasjon? - Elstad, Åsa; Finstad, Bjørn-Petter (Norsk polarhistorie, 2004)
Keywords: Sørishavet; hvalfangstselskaper; hvalindustri; hvalolje; kulturhistorie; pelagisk; politikk; økonomi

Pan-African extension and near-isothermal exhumation of a granulite facies terrain, Dronning Maud Land, Antarctica - Engvik, Ane K.; Elvevold, Synnøve (Geological Magazine, 2004)
The Mühlig-Hofmann- and Filchnerfjella in central Dronning Maud Land, Antarctica, consist of series of granitoid igneous rocks emplaced in granulite and upper amphibolite facies metamorphic rocks. The area has experienced high-temperature metamorphism followed by near-isothermal decompression, partial crustal melting, voluminous magmatism and extensional exhumation during the later phase of the late Neoproterozoic to Cambrian Pan-African event. Remnants of kyanite–garnet–ferritschermakite–rutile assemblages indicate an early higher-pressure metamorphism and crustal overthickening. The gneisses experienced peak granulite facies temperatures of 800–900 °C at intermediate pressures. Breakdown of garnet + sillimanite + spinel-bearing assemblages to cordierite shows subsequent re-equilibration to lower pressures. An E–W foliation dominating the gneisses illustrates transposition of migmatites and leucocratic melts which evolved during the near-isothermal decompression. Occurrence of extensional shear bands and shear zones evolving from the ductile partial melting stage through semiductile towards brittle conditions, shows that the uplift persisted towards brittle crustal conditions under tectonic W/SW-vergent extension. Late-orogenic Pan-African quartz syenites intruded after formation of the main gneiss fabric contain narrow semiductile to brittle shear zones, illustrating that the extensional exhumation continued also after their emplacement. The latest record of the Pan-African event is late-magmatic fluid infiltration around 350–400 °C and 2 kbar. At this stage the Pan-African crust had undergone 15–20 km exhumation from the peak granulite facies conditions. We conclude that the later phase of the Pan-African event in central Dronning Maud Land is characterized by a near-isothermal decompression P–T path and extensional structures indicating tectonic exhumation, which is most likely related to a late-orogenic collapsing phase of the Pan-African orogen.
Keywords: Dronning Maud Land; geologi; petrologi

Polarheltene - minner og monumenter - Eriksen, Anne (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; polarfarere; polarområdene

The race for the South Pole: Robert Scott and Roald Amundsen (1911-12) - Fleming, Fergus (Off the map : tales of endurance and exploration, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

"En æressag for vor nation" - Fulsås, Narve (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser

Kappløp i gamle spor - Goksøyr, Matti (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; ekspedisjoner

Klodens helse - sett fra polene - Hessen, Dag O (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; ekspedisjoner; forskning; internasjonalt samarbeid

Firn accumulation records for the past 1000 years on the basis of dielectric profiling of six cores from Dronning Maud Land, Antarctica - Hofstede, Coen M; Roderik, S W van de Wal; Kaspers, Karsten Adrian; van den Broeke, Michiel R; Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Lappegard, Gante; Mulvaney, Robert; Oerter, Hans; Wilhelms, Frank (Journal of Glaciology, 2004)
This paper presents an overview of firn accumulation in Dronning Maud Land (DML), Antarctica, over the past 1000 years. It is based on a chronology established with dated volcanogenic horizons detected by dielectric profiling of six medium-length firn cores. In 1998 the British Antarctic Survey retrieved a medium-length firn core from western DML. During the Nordic EPICA (European Project for Ice Coring in Antarctica) traverse of 2000/01, a 160 m long firn core was drilled in eastern DML. Together with previously published data from four other medium-length ice cores from the area, these cores yield 50 possible volcanogenic horizons. All six firn cores cover a mutual time record until the 29th eruption. This overlapping period represents a period of approximately 1000 years, with mean values ranging between 43 and 71 mm w.e. The cores revealed no significant trend in snow accumulation. Running averages over 50 years, averaged over the six cores, indicate temporal variations of5%. All cores display evidence of a minimum in the mean annual firn accumulation rate around AD 1500 and maxima around AD 1400 and 1800. The mean increase over the early 20th century was the strongest increase, but the absolute accumulation rate was not much higher than around AD 1400. In eastern DML a 13% increase is observed for the second half of the 20th century.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; paleoklimatologi

Southern Ocean climate variability - Nielsen, Simon Harder Holm (University of Tromsø and Norwegian Polar Institute, 2004)
Keywords: Sørishavet; havnivå; holocene; klimaendringer

De tre store - Næss, Atle (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

17th International FRISP Workshop held at the British Antarctic Survey, Cambridge, U.K. on 17th and 18th June 2003 - Smedsrud, Lars H. (Forum for Research into Ice Shelf Processes Report, 2004)
Keywords: Antarktis; Sørishavet; glasiologi; havis